Secretory immunoglobulin A and cardiovascular reactions to mental arithmetic, cold pressor, and exercise: Effects of alpha-adrenergic blockade - Christopher Ring; Lesley K. Harrison; Alexandra Winzer; Douglas Carroll; Mark T. Drayson; M. J. Kendall (2000)
The mechanism underlying acute changes in secretory immunoglobulin A (sIgA) remains to be determined. In this experiment, sIgA and cardiovascular activity were monitored at rest and while participants performed a mental arithmetic task, cold pressor, and submaximal cycle exercise following placebo or 1 mg of the alpha-adrenergic blocker, doxazosin. Under placebo, the tasks produced patterns of cardiovascular activity indicative of combined alpha- and beta-adrenergic, alpha-adrenergic, and beta-adrenergic activation, respectively. Doxazosin was associated with reduced blood pressure during cold pressor, but not during arithmetic or exercise. Mental arithmetic elicited increases in sIgA concentration and exercise produced increases in both sIgA concentration and secretion rate; these changes were unaffected by alpha blockade. In contrast, the cold pressor was associated with decreases in both sIgA concentration and secretion rate, which were blocked by doxazosin. These data suggest that acute decreases, but not increases, in sIgA are mediated by alpha-adrenergic mechanisms.